Multi-Utilities and Access : Can Private Multi-Utilities Help Expand Service to Rural Areas? - Tremolet, Sophie (World Bank, Washington, DC, 2012)
In 1997 Gabon awarded the first real concession in Africa, under a contract that introduced coverage targets for expanding service to previously unconnected rural areas. SEEG, the new concessionaire, offers both water and electricity service, with the electricity business cross-subsidizing the less developed water business. Five years on, the concessionaire has performed well in established service areas, often exceeding targets, but has made less progress in more isolated areas. This Note assesses lessons for the design of contracts with incentives for expanding service beyond the immediate circles of major urban centers-and on the potential role of multi-utilities.